Trade Reform and Household Welfare : The Case of Mexico - Ianchovichina, Elena; Nicita, Alessandro; Soloaga, Isidro (World Bank, Washington, DC, 2014)
The authors use a two-step, computationally simple procedure to analyze the effects of Mexico's potentially unilateral tariff liberalization. First, they use a computable general equilibrium model provided by the Global Trade Analysis Project (GTAP) as the new price generator. Second, they apply the price changes to Mexican household data to assess the effects of the simulated policy on poverty and income distribution. By choosing GTAP as the price generator, the authors are able to model Mexico's differential tariff structure appropriately: almost zero for North American Free Trade Agreement (NAFTA) members and higher tariffs for nonmembers. Even starting with low tariff protection, simulation results show that tariff reform will have a positive effect on welfare for all expenditure deciles. Under an assumption of nonhomothetic individual preferences, trade liberalization benefits people in the poorer deciles more than those in the richer ones.